The archaeology of animal bones - O'Connor, T. P. (Terence Patrick) 1954- (Great Britain Sutton Publishing Limited, 2004)
The author provides a focused overview of the field, emphasizing how bones are used to study past human-animal interactions.
1. Why Study a Lot of Old Bones? -- 2. Bone, Bones and Skeletons -- 3. Taphonomy: From Life to Death and Beyond -- 4. Excavation and Recovery -- 5. Identification and Description -- 6. Counting Bones and Quantifying Taxa -- 7. Out on a Limb: Body-Part Quantification -- 8.Estimation of Age at Death -- 9. Palaeopathology: Understanding Sickness and Injury -- 10. Metrical and NonMetrical Variation -- 11. Climate, Environment and Small Vertebrates -- 12. Hunting and Fishing: People as Predators -- 13. Settling Down: The Domestication of Animals and People -- 14. Urban Garbage: On Drovers, Butchers, Wealth and Rats -- 15. More than Just Old Bones.
Originally published : Stroud : Sutton, 2000.
Includes bibliographical references (p. 177-200) and index.
Keywords: Animal remains (Archaeology); Archaeolog -- Methodology; Bones